Islamic State of Afghanistan : Staff Report for the 2003 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The authorities have made solid progress in rebuilding institutions and implementing sound economic policies, although huge challenges still remain. The IMF has been providing extensive policy advice and technical assistance to the authorities. With the help of the international community, the authorities have made impressive strides in rebuilding institutions and implementing sound economic policies. The economic recovery is strong, but comes from a very low level. Preliminary data suggest that expenditures were again off to a slow start in 2003/04.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet